A method for testing indoxacarb residues in three vegetables and the dietary risk assessment - Ai Liu; Fengyu Li; Jiacheng Ge; Guodong Si; Xianzheng Han; Yun Gao; Wenli Wang; Li Su; Nan Zou; Wei Mu; Xiaomei Li; Xiuyu Pang (Applied Food Research)
This study focuses on the development and validation of a detection method for indoxacarb residues in three major vegetable crops, Chinese cabbage, cabbage, and tomato, which are widely cultivated worldwide. The method was rigorously validated through field trials and dietary risk assessment. A strong linear response was observed for indoxacarb at the concentrations of 0.0005 - 0.25 mg/L, with a limit of quantitation of 0.01 mg/kg. The half-life of indoxacarb ranged from 4.61 to 6.89 days in Chinese cabbage, 3.06 to 6.21 days in cabbage, and 2.28 to 3.46 days in tomato. The terminal residues were <0.01 - 0.2 mg/kg in Chinese cabbage, <0.01 - 0.15 mg/kg in cabbage, and <0.01 - 0.029 mg/kg in tomato. Dietary risk assessment revealed a low probability of long-term risk (12.9 %) associated with the consumption of these crops. Overall, the study suggests that the use of indoxacarb on these three vegetables is safe for the general population, with minimal risk even under long-term exposure.